Conceptualizing Time Preference: A Life-History Analysis. (1st October 2014) - Copping, Lee T.; Campbell, Anne; Muncer, Steven
Life-history theory (LHT) has drawn upon the concept of "time preference" as a psychological mechanism for the development of fast and slow strategies. However, the conceptual and empirical nature of this mechanism is ill-defined. This study compared four traits commonly used as measures of "time preference" (impulsivity, sensation seeking, future orientation and delay discounting) and evaluated their relationship to variables associated with life-history strategies (aggressive behavior and mating attitudes, biological sex, pubertal timing, victimization, and exposure to aggression in the environment). Results indicated that only sensation seeking consistently showed all the predicted associations, although impulsivity, future orientation, and delay discounting showed some significant associations. A unidimensional higher-order factor of "time preference" did not adequately fit the data and lacked structural invariance across age and sex, suggesting that personality traits associated with LHT do not represent a global trait. We discuss the use of personality traits as measures in LHT and suggest that greater caution and clarity is required when conceptualizing this construct in future work.